EFFECTS OF ANESTHESIA ON INNATE IMMUNE COMPONENTS IN ORTHOPEDIC SURGERY - Aubaid, Adnan Hamad; Yassen, Khalid Lahmood (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The present study was carried out to evaluate the possible role of anesthetics and surgery on innate by measuring the levels of tumor necrosis factor alpha (TNFÎ±) and interferon gamma (IFNÎ³) by enzyme-linked immunosorbent assay (ELISA). Flow cytometry was used to determine MCP-I and CD16. Methods: Serum level of TNFÎ± and IFNÎ³ cytokines was measured using ELISA technique. Flow cytometry was used to determine MCP-I and CD16. White blood cell count and C-reactive protein (CRP) were determined. Results: There was a highly significant rise in CRP blood level postoperatively when compared with pre-operative blood level (p<0.001). In addition, the results revealed a significant rise in neutrophil count after operation in comparison with its baseline level before operation (p<0.001), while the level of lymphocytes showed significant decline following operation (p<0.001). The level of monocyte and eosinophil also got significantly reduced after operation (p<0.001), whereas the level of basophil showed no significant alteration after operation (p=0.687). CD16 NK cell count revealed a significant rise during the time of anesthesia. However, it showed a significant decrease postoperatively, but the reduction did not reach baseline count. It has been noticed also that the level of MCP-1 got raised significantly in association with anesthesia induction; however, it returned back to its baseline level following surgery. Conclusions: Analysis of data to correlate the innate immune components TNFÎ±, IFNÎ³, MCP-I, and CD16 with types of anesthetic drugs (general, local, and regional anesthesia) showed no significant association between these components and type of anesthesia (p>0.05).